Determinación de algunas propiedades físicas y mecánicas de Grevillea robusta A. Cunn. del estado de Veracruz - Zárate Morales, Reyna Paula; Ordóñez Candelaria, Víctor Rubén; Martínez Castillo, José Luis (Instituto de Ecología, A.C., 2016)
The physical and mechanical properties of Grevillea robusta A. Cunn. were determined, testing small clear specimens. The testing material was obtained from  two trees collected in the central region of Veracruz state. The mechanical properties were determined in green and dry condition. The material for tests in dry condition was obtained from the drying tests. A high ratio between tangential and radial contraction was calculated, which could be construed as an indication of low dimensional stability; however, from these experiments pieces with minimum distortions resulted. The tests carried out were: static bending, compression and shear parallel to grain, compression perpendicular to grain, end hardness and side hardness (radial and tangential directions) and toughness. In this paper the mean values, the standard deviation and the coefficients of variation are reported for all properties mentioned. Taking into account the abundance of multiseriate rays which can be with the naked eye, and estimate of the percentage of area in the tangential section was determined and high values of this percentage were found which might have an influence on the mechanical strength of the of this species. It was found that this wood has a strength from low to medium.